21st century timber engineering : proceedings of a session sponsored by the Committee on Wood of the Structural Division of the American Society of Civil Engineers in conjunction with the ASCE Convention in Dallas, Texas, October 24-28, 1993 - Cheung, Kevin C. K. (American Society of Civil Engineers, 1993)
Technological advances, governmental mandates, and environmental concerns are important factors to the development of timber engineering in the 21st century. New uses of wood and new wood products are just two examples of the latest innovations in the discipline. This collection of four state-of-the-art papers reveals the current status of timber engineering and what can be expected in the next century. Topics covered include the seismic design of multi-story, wood-framed buildings; load and resistance factor design for wood construction; structural fire resistance design of wood beams and columns; and environmental considerations when using wood as structural material.